Four-fermion production near the W pair production threshold - Beneke, M; Falgari, P; Schwinn, C; Signer, A; Zanderighi, G (2007)
We perform a dedicated study of the four-fermion production process e- e+ -> mu- nubar_mu u dbar X near the W pair-production threshold in view of the importance of this process for a precise measurement of the W boson mass. Accurate theoretical predictions for this process require a systematic treatment of finite-width effects. We use unstable-particle effective field theory (EFT) to perform an expansion in the coupling constants, GammaW/MW, and the non-relativistic velocity v of the W boson up to next-to-leading order in GammaW/MW ~ alpha_ew ~ v^2. We find that the dominant theoretical uncertainty in MW is currently due to an incomplete treatment of initial-state radiation. The remaining uncertainty of the NLO EFT calculation translates into delta MW ~ 10-15 MeV, and to about 5 MeV with additional input from the NLO four-fermion calculation in the full theory.